Review of Writing Out of Limbo: International Childhoods, Global Nomads and Third Culture Kids - Costa, Rosalina (2015)
There is something mysteriously enticing in both the cover and content of Writing Out of Limbo that will not leave whoever reads it indifferent, whether coming from the general audience and freshly seduced by the title, or being the most specialized professor and researcher from the college and academy. The book, edited by Gene H Bell-Villada and Nina Sichel, with Faith Eidse and Elaine Neil Orr, brings together 31 scholarly articles and personal essays on international childhoods, Global Nomads and Third Culture Kids. In the initial pages, two key definitions are included to clarify the main topic. A Third Culture Kid (TCK, also designated 3CK) is, according to David C Pollock and Ruth E Van Reken, ‘a person who has spent a significant part of his or her developmental years outside the parent’s culture’. Likewise, a Global Nomad (GN) is, quoting Norma M McCaig, ‘anyone of any nationality who has lived outside their parent’s country of origin (or their “passport country”) before adulthood because of a parent’s occupation’. The time a TCK spends abroad may range from one to several years covering the childhood and/or adolescence; such an experience can be circumscribed to single place or multiple locations. The underlying reasons can also vary greatly according to the parent’s occupational backgrounds (e.g. business, missionary, foreign-service or military).